A New Wavelet Method for Identification of Eddies and Assessment of Incidents on Islands of the Eastern Caribbean. Issue 3 (4th May 2019) - Tambie, Jason D.; Farag-Miller, Madiha; Miller, Keith; Ramlal, Bheshem; Sutherland, Michael
Abstract: Using two dimensional continuous wavelet transforms, a novel method for identification of mesoscale eddies is presented to facilitate extraction of characteristics for area, amplitude, type, and location from maps of sea level anomalies. In comparison with the previously established growing method for eddy identification, it is found that the wavelet method identifies more than twice the number of eddies and is particularly better at resolving small eddies down to the 0.25 degree resolution of the data. Such research into eddy identification and tracking is significant to the assessment of eddies with potential to impact on coastlines of small islands. The method is applied to the identification of eddies on tracks towards islands of the Eastern Caribbean over 23 years. Spatial and temporal variation in rate of occurrence and magnitude is established. For Barbados there is an average of 9 anticyclonic incidents a year with maximum amplitude of typically 0.22 m in the dry seasons and 0.16 m in the wet seasons. Seasonal variation is reversed for the other islands with twice the number of anticyclonic incidents having maximum amplitudes of about 0.20 m annually.